Pemanfaatan Media Digital Canva dalam Menopang Digitalisasi Manajemen Pancasila pada OSIS SMA YPPK Teruna Bakti - Ade Sopyan Hadi; Maya Mashita; Ricky Engel Mawara; Petrus Irianto; Willius Kogoya; Muhammad Aqil (Universitas Cenderawasih, 2026)
The development of digital technology in the era of the Industrial Revolution 4.0 and Society 5.0 requires student organizations to be able to adapt to digital transformation in managing organizational activities. However, the OSIS management of YPPK Teruna Bakti High School still faces limitations in creating publication media, documenting activities, and managing organizational information digitally. This community service activity aims to improve the digital literacy of OSIS administrators through the use of Canva digital media while supporting the digitalization of Pancasila Management in student organizations. The method used in this community service is the Participatory Training and Mentoring approach (participatory training and mentoring) which involves OSIS administrators as active participants in the training, practice, and evaluation process. The results of this community service are activities carried out for 15 OSIS administrators through training in creating various digital media, especially Canva-based OSIS chairperson candidate campaign posters that integrate Pancasila democratic values. The results of this community service activity show that participants are able to develop more creative, attractive, and communicative digital publication media, and understand the use of technology as a means of strengthening Pancasila values. The conclusion of this community service activity is that the use of Canva has proven effective in supporting the digitalization of school organizational management while supporting the formation of student character that is creative, democratic, responsible, and adaptive to technological developments.